"They Gave the Children China Dolls": Toys, Socialization, and Gendered Labor on American Plantations. (4th May 2022) - Betti, Colleen
ABSTRACT: Play has long been understood to be a key aspect of childhood socialization into gender roles, including gendered labor. Yet, some have reasonably assumed that enslaved children on plantations in the United States had little time for play and that any toys owned by them would have been homemade and thus difficult to later identify archaeologically. Evidence from slavery-related sites in the Digital Archaeological Archive of Comparative Slavery (DAACS), however, demonstrates that formal toys in the form of porcelain dolls, toy dishes, marbles, and military toys were not uncommon possessions for enslaved children in the American South. The recovery of formal toys in living quarters used by enslaved people is especially surprising given that their intended socialization messages did not align with the future gendered labor roles of enslaved children. These toys thus reveal the complicated socializing forces and messages about gendered labor that enslaved children encountered through play.